EVALUATION OF PRODUCTION FACTORS AND THEIR EFFICIENCY IN DAIRY FARMS LOCALIZED IN THREE REGIONS OF LUBELSKIE VOIVODESHIP - Jolanta Bojarszczuk; Jerzy Księżak (Acta Scientiarum Polonorum. Oeconomia, 2010)
The paper presents evaluation of production factors and the efficiency of their use in selected dairy farms in Lubelskie voivodeship. The method, which was used during the research, was based on survey investigation. The analysis showed, that the analysed farms, despite limited investment, were sufficiently equipped. They had at disposal labour and capital resources as main factors of production. There were some differences in efficiency of production factors use in the farms, depending on a region. Farms in Ryki region had better results, regarding a direct surplus per 1 ha UAA and high capital effectiveness.